AstroWealth: Personal Finance Management Web Application - Jasmin, Putri; Suhaila (Applied Information Technology And Computer Science, 2024)
AstroWealth is a comprehensive personal finance management web application specifically designed to assist university students in building and managing their wealth as they transition into adulthood, all while receiving support from their parents. Many students today continue to rely on outdated and traditional methods for financial management, which have often proven to be inefficient and inadequate in addressing the unique challenges they face. Recognizing these limitations, AstroWealth offers a collaborative and modern approach that underscores the significance of parental involvement and thorough personal finance management, particularly crucial in an era where educational expenses are increasing. AstroWealth comprises eight distinct modules, each serving a specific purpose to enhance the overall user experience. The application is developed using an object-oriented approach and PHP, a widely-used server-side scripting language. By combining modern development practices with a focus on collaborative financial management, AstroWealth stands out as a vital tool in today’s demanding educational landscape.